The Biennial Reader : The Berjen Biennial Conference - Elena Filipovic (editor); Marieke Van Hal (editor); Solveig Ovstebo (editor) (Hatje Cantz Verlag; Bergen Kunsthall, 2010)
Volume on one of the largest international conferences on biennials, Bergen Biennial Conference, Bergen, Norway.
English
Keywords: Biennial exhibition theory; N4390-5098 Visual Arts- Exhibitions